(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
This research investigates the importance of social accounting and the auditor’s report. It basically checks if there is an impact of social accounting on the auditor’s report at the availability the INTOSAI standards No. (1700 and 1706). The study recruited 105 employees of the Federal Financial Supervision Office in Iraq. Data were collected using questionnaire. The questionnaire validity and reliability were checked to assure the truthfulness of the findings. The study found a positive correlation and a statistically significant effect between the accounting for social responsibility and the auditor’s report. It is necessarily recommended for the auditor and the bodies working in the Board of Supreme Audit to ensure the inclusion of a paragraph that draws attention in the report prepared in accordance with the INTOSAI standards (1706) regarding the extent of adequate and appropriate disclosure of the social responsibility of the entities subject to audit.